Government policies and ethnic relations in Asia and the Pacific - Brown, Michael E. (Michael Edward), 1954-; Ganguly, Sumit (Cambridge, Mass. : MIT Press, 1997)
This volume analyzes different policies that governments have pursued in their efforts to contend with the tensions inherent in multiethnic societies. The book focuses on Asia and the Pacific, the most populous and economically vibrant part of the world. The heart of the book is a set of case studies of government policies in sixteen countries: India, Pakistan, Sri Lanka, Burma, Thailand, Malaysia, Singapore, Indonesia, the Philippines, China, Australia, New Zealand, Papua New Guinea, Fiji, Vanuatu, and the Federated States of Micronesia. The studies consider a wide range of political, economic, educational, linguistic, and cultural policies, and evaluate how these policies have evolved over time. Using a broad comparative perspective to assess the effectiveness of different governmental approaches, the authors offer policy recommendations that cut across individual countries and regions.
Ch. 12. Culture and Conflict in Fiji, Papua New Guinea, Vanuatu, and the Federated States of Micronesia / Stephen Levine -- Ch. 13. The Impact of Government Policies on Ethnic Relations / Michael E. Brown -- About the Belfer Center for Science and International Affairs.
"In cooperation with the Pacific Basin Research Center."
Includes bibliographical references (p. [577]-590) and index.
Keywords: Multiculturalism -- Asia; Multiculturalism -- Pacific Area; Asia -- Ethnic relations -- Government policy; Pacific Area -- Ethnic relations -- Government policy; Asia -- Politics and government -- 1945-; Pacific Area -- Politics and government